Physiological quality and aflatoxins prevalence in conventional and transgenic soybeans during storage (Bioscience Journal, 2019)
Physiological quality of soybean seeds of five varieties (CD 215, CD 202, CD 233RR (GMO), NK and NK 412113 7059RR (GMO)), stored under cooling and room temperature during eight months as well as B1, B2, and G2 aflatoxins prevalence were evaluated. The tests (moisture content, germination, tetrazolium) were performed before storage and every 60 days. The analysis of aflatoxins presence was carried out at the beginning and at each two months. Two samples of each variety were stored at -4 °C until analysis processing, then high-performance liquid chromatography analysis was used. The seeds showed, in general, water content between 11 and 13% until 60 storage days, whose decrease began up from 120 days. At 60 storage days, the cooled seeds had higher germination percentage when compared to the ones kept under room temperature. In relation to the studied varieties, the highest germination was recorded for CD 215, which differed from CD 202 in both periods. There were factors interactions after 120 and 240 storage days, especially under cooling to 120 days for CD 215 variety. While, at 240 days under room temperature was observed the highest germination for the CD 233 RR. The storage conditions were significant at 60, 180 and 240 days for viability, with a higher rate for seeds stored under cooling. Regarding varieties, over the same periods, the CD 202 variety showed lower viability percentage, with NK 412 113 after 180 and 240 days. In general, 90 samples were tested and, 25 were detected the aflatoxins presence. It was observed that the aflatoxins presence in CD 202 was quantitatively greater from 16 tested samples 10 showed some level of aflatoxin contamination. AFB1 and AFB2 aflatoxins represented 50%, while AFG2 was observed in 63% of those samples. There was no difference in relation to seed vigor between conventional or transgenic soybeans seeds. Cooling kept the vigor of CD 215 and CD 233RR varieties until the final of the experiment. There was no influence by the storage to get aflatoxins and temperature association.